Optical properties of LiNbO3:B crystals - N.V. Sidorov; M.V. Smirnov; R.A. Titov; N.A. Teplyakova; M.N. Palatnikov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2022)
The optical properties of nominally pure LiNbO3stoich, near-stoichiometric LiNbO3stoich (6,0 wt% K2O), LiNbO3cong and LiNbO3:B (0,55 and 0,83 mol% B2O3 in the charge) crystals in the visible region of the spectrum (λ = 380-700 nm) were studied by photoluminescence. LiNbO3:B crystals were grown by Czochralski using the technology of a direct solid-phase doping of the congruent charge by boron oxide (B2O3). The photoluminescence intensity increases in the series of crystals: LiNbO3stoich, LiNbO3stoich (6,0 wt% K2O), and LiNbO3cong. The photoluminescence intensity is determined by the concentration of deep electron traps (NbLi – «niobium antisite») and the stoichiometry of these crystals. The photoluminescence intensity of LiNbO3:B (0,55 and 0,83 mol% B2O3 in the charge) crystals is close to the photoluminescence intensity of LiNbO3stoich crystal. This can be explained by the fact that the composition and structure of LiNbO3:B (0,55 and 0,83 mol% B2O3 in the charge) crystals approach the composition and structure of the stoichiometric crystal.